Eksistensi Konflik Di Dalam Organisasi - Muspawi, Mohamad; Rahman, Indah Afidah; Hanapi, Muhammad Harli (Jurnal Ilmiah Dikdaya, 2023)
Conflict within the organization can affect individuals within the organization. Conflicts that are not handled properly can hinder organizational communication and hinder the creation of cooperation between individuals within the organization. This study aims to determine the effect of conflict on individuals in organizations. This study uses qualitative research methods with literature study techniques by collecting data from various sources such as books, journals, and references. This study aims to know and understand how conflict affects an individual in an organization. The results of the research show that this can affect individuals within an organization so it can affect the performance of each individual. This research is expected to contribute to the development of theory and practice of human resource management in organizations.